Disbudding pain: The benefits of disbudding goat kids with dexmedetomidine hydrochloride - Nfor, Oswald Ndi; Chan, Jacky Peng-Wen; Kere, Michel; Peh, Huo-Cheng (Small ruminant research, 2016)
•Disbudding, a stressful and painful procedure is increasingly becoming an everyday practice in dairy goat farms.•Kids were disbudded using different disbudding pre-medications.•Plasma cortisol levels were significantly higher in kids that were hot-iron disbudded without treatment, and those that received lidocaine and meloxicam.•Kids that were disbudded under sedation with dexmedetomidine hydrochloride showed negligible signs of pain. This study compared the effectiveness of intramuscularly administered dexmedetomidine hydrochloride and other pharmacologic techniques used in reducing disbudding pain in goat kids. A total of 30 kids aged 4–9days old were randomly assigned to 5 treatment groups; Sham disbudded (SD, n=6); hot-iron disbudded (295–326°C, 4–7s/horn bud; D, n=6); hot-iron disbudded after a ring block with lidocaine hydrochloride and IM administration of meloxicam (LMD, n=6); hot-iron disbudded under dexmedetomidine hydrochloride, lidocaine hydrochloride and meloxicam (DeLMD, n=6); hot-iron disbudded under dexmedetomidine hydrochloride and saline (DeSSD, n=6). Results indicated that there were significant increases in plasma cortisol of the D (pre-disbudding, 16.97±3.3 vs. after disbudding, 58.1±12.8, mean±SE) and LMD (15.2±3.0 vs. 43.9±8.6: P<0.05). However, the levels were slightly higher but insignificant among the sedated kids. The mean cortisol of the DeSSD kids was significantly low during 5h after disbudding (11.2±2.5, p=0.0436). The total means of the pain-related behaviors were significantly high in the D and LMD kids whereas the sedated kids had relatively low values (P<0.05). The DeSSD group had the lowest number of pain-related behaviors. Heart rates and rectal temperature decreased significantly in the DeSSD kids. There were no significant differences in respiration rates among all the kids. The cortisol and behavior levels observed in this study suggest a positive reduction in pain among kids disbudded under sedation with dexmedetomidine hydrochloride. It was concluded that sedation with dexmedetomidine hydrochloride prior to disbudding can improve kid’s welfare.